Biological poisons targeting the pituitary gland: insights across the five kingdoms - Sanchis-Pascual, David; Cámara Gómez, Rosa; Morillas-Amat, Pilar; Lara-Gálvez, Darío; Pérez-Cervantes, Víctor; Masdeu-López-Cerón, Pilar; Merino-Torres, Juan Francisco (Frontiers in Endocrinology, 2025)
The pituitary gland, as a central regulator of endocrine function, may be affected by a wide range of biologically derived harmful substances present in nature. While most available literature focuses on neoplasms, trauma or autoimmune disorders, the potential impact of natural toxins and poisons on pituitary function remains underexplored. This narrative review addresses the effects of acute or chronic exposure to harmful agents originating from the five biological kingdoms—Animalia, Plantae, Fungi, Monera, and Protista—on the hypothalamic–pituitary axis. Drawing on clinical reports, experimental data, and physiological insights, we describe how various biological substances may alter hormonal regulation, leading to temporary or persistent dysfunction. Importantly, this review does not cover direct infectious involvement of the pituitary, such as pituitary abscess, but focuses instead on biologically active compounds produced by living organisms. The review highlights a dispersed body of knowledge with implications not only for endocrinologists and pituitary specialists, but also for clinicians in toxicology, emergency medicine, infectious diseases, and global health. Recognizing the pituitary as a vulnerable target in diverse environmental and ecological contexts may aid in the early diagnosis and management of otherwise unexpected endocrine disorders.